Historic buildings resilience: A view over envelope energy retrofit possibilities - Vasco Peixoto de Freitas (2018)
2018 is the European Year of Cultural Heritage, officially defined by the European Parliament and Council in May 2017. Therefore the need of defining and promoting good practices in conservation and enhancement of historic buildings in Europe is much a current issue. In the last decades, an increasing attention has been paid to the improvement of energy performances and indoor thermal comfort in existing constructions to guarantee their reuse and keep them alive. Moreover, historic buildings, by definition durable and resilient constructions, should be prepared for the new challenges of climatic changes. The present study considers strategies, technologies and materials proposed in literature for historic buildings energy and thermal retrofit, focusing particularly on envelope refurbishment interventions. The suitability of the solutions for preserving historic valuable constructions is also accounted, mainly via considering the principle of authenticity and vapour permeability for compatibility. The efficacy of the interventions, in terms of energy savings, is then investigated. Results show that existing solutions can lead to significant decreases in buildings energy consumption, 22% to 51% averagely, but only part of them appears suitable for historic buildings preservation.